2019
DOI: 10.3389/fnbot.2019.00104
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Coordination of Flexible Limbs: Decentralized Control Scheme for Inter- and Intra-Limb Coordination in Brittle Stars' Locomotion

Abstract: Conventional mobile robots have difficulties adapting to unpredictable environments or performing adequately after undergoing physical damages in realtime operation, unlike animals. We address this issue by focusing on brittle stars, an echinoderm related to starfish. Most brittle stars have five flexible arms, and they can coordinate among the arms (i.e., inter-arm coordination) as well as the many bodily degrees of freedom within each arm (i.e., intra-arm coordination). They can move in unpredictable environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In lampreys, complete transection of the rostral spinal cord leads to immediate paralysis, after which locomotor behaviours like swimming and burrowing gradually return over the course of a few months (Fig. 3A, top) (Rovainen, 1976;Selzer, 1978;Cohen et al 1986;Oliphint et al 2010;Katz et al 2020). Remarkably, lampreys can recover nearly normal swimming after one or two complete spinal transections (Fig.…”
Section: Locomotor Network Undergo Long-term Reorganization To Restor...mentioning
confidence: 97%
“…In lampreys, complete transection of the rostral spinal cord leads to immediate paralysis, after which locomotor behaviours like swimming and burrowing gradually return over the course of a few months (Fig. 3A, top) (Rovainen, 1976;Selzer, 1978;Cohen et al 1986;Oliphint et al 2010;Katz et al 2020). Remarkably, lampreys can recover nearly normal swimming after one or two complete spinal transections (Fig.…”
Section: Locomotor Network Undergo Long-term Reorganization To Restor...mentioning
confidence: 97%
“…Previous research (Owaki et al, 2012 , 2017 ; Barikhan et al, 2014 ; Aoi et al, 2017 ; Kano et al, 2017b , 2019 ; Ambe et al, 2018 ) has shown the possibility of offloading the task of interlimb coordination toward body-environment interactions and adaptation to physical damage. By using sensory feedback to trigger reactions in local (decentralized) CPGs and drive individual leg movements, this approach is able to form walking patterns in robots without direct control over the interlimb coordination process.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps an inertial measurement unit (IMU) placed at the center of mass could drive rotations and undulations at key points, such as the nose, pectoral, and pelvic regions. Feedback from these points in conjunction with current advances in control algorithms (Santos and Matos, 2012;Koos et al, 2013;Kano et al, 2019) could allow the robot to tune a baseline axial CPG into a hybrid gait suitable for whatever force environment it's in. Then, the robot could not only transition from aquatic to terrestrial locomotion but also deal with a range of perturbations from bumps in the road to loss of body parts.…”
Section: Insights For the Control Of Limbed Robotsmentioning
confidence: 99%
“…The field of robotics and control could learn a lot from how animals control motion and adapt to extreme perturbations such as the loss of one or more limbs (Trimmer and Lin, 2014;Chattunyakit et al, 2019;Kano et al, 2019). This is especially important for robots deployed in the field for long term missions such as deep sea or space exploration (Koos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation